Multisensory integration in quarter note beat precision - Paappanen, Mikko Pekka (2024)
Multisensory integration concerns the integration of different sensory signals combined into a new product. Due to the technological advancements of recent years, the field of multisensory research has expanded in many different industries. This thesis investigates multisensory integration in a musical context, more specifically, in musical beat-based timekeeping. Previous research has demonstrated musicians’ ability to utilize multisensory integration in reaction time tests. The goal of this study is to investigate auditory, haptic, and auditive-haptic beat precision using a commercially available metronome solution. Experimental quantitative research design was selected as the method of research. The research data consists of 10 musically active individuals. Two rhythmic playing tasks were given to the participants for establishing beat precision values which were analyzed using a modern audio analysis framework. The results for the first long duration playing task indicate no significant differences between the sensory modalities. The results for the second experiment with tempo changes indicate the haptic sensory modality is the most precise in terms of beat precision. Positive benefits of multisensory integration were not perceived in the results. This thesis provides future research agendas regarding improvements on how to measure multisensory beat precision.